Home Learning Facilitation of Parents on their Children in the Modular Learning Modality - Wilter C. Friales; Loveleih G. Quemado; Sheila B. Bayog (CV. Literasi Indonesia, 2022)
Home Learning Facilitation of parents refers to the role of the parents in guiding and mentoring their children who are into Modular Learning Modality. While learning at home, this learning modality requires a great extent of support from parents as learning facilitators to ensure students’ learning progress. This study aims to describe home facilitation as experienced by the parents in the selected remote areas in region 12. This is qualitative research employing a descriptive phenomenological approach using Collaizi’s approach on thematic analysis. Themes on Building the character and setting life’s goals; Motivating children to pursue education; learning facilitative pedagogical approaches in mentoring their children, and their shared insights have emerged in understanding the essence of Home Learning Facilitation of Parents on their Children.